Patterns of Lip-prints in Undergraduate Medical Students of Bahawalpur - Hira Anjum, Hira Munir, Aftab Ali Ummara Munir, Tehreem Abaid, Talha Naeem Cheema (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the frequency of different lip patterns among medical students. Study Design: Cross Sectional Study (Descriptive) Setting and Duration of Study: Department of Forensic Medicine & Toxicology, QAMC/ Bahawal Victoria Hospital, Bahawalpur. From 15th January 2018 to 14 March 2018 Materials and Methods: Total 203 of medical students 18-25 years of age of and both genders was selected. Subjects with any lip deformity or allergic episode with lip stick were excluded. After application of a dark colored, non-glossy, less moist lipstick on lips, lip-prints were obtained on a cellophane tape and then pasted on A4 paper. Results: Out of these 203 subjects, 110 (54.19%) were men and 93 (45.81%) were women with M:F ratio of 1.2:1. In this study, Type I (26.11%) and Type II (20.69%) was the utmost communal lip patterns, trailed by Type-I’ (18.72%), Type III (18.23%), Type IV (10.34%) and Type V (5.91%). Conclusion: This study concluded that cheiloscopy and its pattern recognition in varying circumstances provide valuable information with regards to identification of an individual. Keywords: Cheiloscopy, Identification, Fingerprinting, Geographical Area